Health service utilization care for adolescents: A literature study - Suryani, Lilis; Najmah, Najmah; Zulkarnain, Mohammad (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Adolescents or young children are referred to as people aged between ten and eighteen years. Adolescence is a transition period for young children experiencing many problems within themselves and their environment, from childhood to adulthood. If young children cannot identify these evocations correctly, they are sure to face many problems. In this teenage phase they are no longer called children and are not called adults. Adolescents today face more complex expectations, demands, temptations and dangers compared to previous generations of teenagers. The phenomenon is that most teenagers in Indonesia today experience a decline in character, morals and emotional maturity.Purpose: To review previous research in analyzing the relationship between health service utilization care for adolescents.Method: Use a literature review by determining keywords, creating questions, grouping questions, answering questions. Researchers collect data through various sources, such as scientific articles, books and institutional reports. This literature review was compiled using Google Scholar, Pubmed, and Semantic Scholar and obtained 14 journals with the keywords